2011
DOI: 10.1182/blood-2010-06-289082
|View full text |Cite
|
Sign up to set email alerts
|

Heparin: a potent inhibitor of hepcidin expression in vitro and in vivo

Abstract: Hepcidin is a major regulator of iron homeostasis, and its expression in liver is regulated by iron, inflammation, and erythropoietic activity with mechanisms that involve bone morphogenetic proteins (BMPs) binding their receptors and coreceptors. Here we show that exogenous heparin strongly inhibited hepcidin expression in hepatic HepG2 cells at pharmacologic concentrations, with a mechanism that probably involves bone morphogenetic protein 6 sequestering and the blocking of SMAD signaling. Treatment of mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 57 publications
5
117
0
3
Order By: Relevance
“…Heparin was recently reported to be a potent inhibitor of liver-derived hepcidin production [27]. In pilot experiments, the qRT-PCR results indicated that hepcidin expression was suppressed in all 3 human hepatic cell lines, HepG2, SMMC-7721 and L-02 (by N50%, Fig.…”
Section: Reduction Of Hepatic Hepcidin Suppressed Tumor Growthmentioning
confidence: 82%
“…Heparin was recently reported to be a potent inhibitor of liver-derived hepcidin production [27]. In pilot experiments, the qRT-PCR results indicated that hepcidin expression was suppressed in all 3 human hepatic cell lines, HepG2, SMMC-7721 and L-02 (by N50%, Fig.…”
Section: Reduction Of Hepatic Hepcidin Suppressed Tumor Growthmentioning
confidence: 82%
“…68 Poli and colleagues demonstrated that heparin inhibited hepcidin expression in hepatic cell lines as well as in mice. 69 Daily injections in mice for seven days (50 mg/kg/d) decreased hepcidin mRNA expression and SMAD phosphorylation, increased serum iron and reduced spleen iron concentration. In 5 patients treated with low molecular weight heparin to prevent deep vein thrombosis, serum hepcidin concentration decreased by 80-85% within 2-5 days after the start of the treatment.…”
Section: Class 1: Decreasing Hepcidin Productionmentioning
confidence: 98%
“…To address this, Poli and colleagues recently prepared non-anticoagulant heparins 70 that retained BMP-modulating activity and potently suppressed hepcidin in vitro and in mice in vivo, also in the presence of an inflammatory stimulus. Interestingly, heparin is also known to have anti-inflammatory activity 69 and this could further contribute to its usefulness for the treatment of iron-restricted disorders.…”
Section: Class 1: Decreasing Hepcidin Productionmentioning
confidence: 99%
“…These and some N-acyl analogues showed beneficial effects in inflammation myocardial ischemic and reperfusion injury [5], inhibitory activity of angiogenesis and metastasis [89] in a broad spectrum of experimental models. An oversulfated LMWH preparation was found beneficial in an iron restricted anaemia model through inhibition of the peptide hormone Hepcidin [68]. Various types of derivatives, chemical processes, some biological interactions and activities are reported in dedicated reviews [87,89,92,93].…”
Section: Sulfation Degree Modificationsmentioning
confidence: 99%
“…Allergic encephalomyelitis [5] Auto-immuno diseases [61] Anti-complement [29,62,63] Anti-atherosclerosis [64] Diabetic nephropathies [26,65] Emphysema [66,67] Iron-restricted anemia [68] Neuroprotection [60] Osteogenesis [69] Periodontal diseases [70] Cystic fibrosis b [80] Emphysema b Fraxiparine [81] Hematopoiesi c [82] Obstetrics c,e Dalteparin [83] Retinal angiogenesis c Suloparoid d [84] Ulcerative colitis c LMWHs [9] a Anecdotal trial; b experimental models; c clinical trials; d LMW heparan sulfate; e shorter human labor.…”
Section: Sulfation Degree Modificationsmentioning
confidence: 99%